2007
DOI: 10.2337/dc06-2192
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Treatment Has No Effect in Patients With Type 2 Diabetes in a Western Population

Abstract: OBJECTIVE -Chromium treatment has been reported to improve glycemic control in patients with type 2 diabetes. However, concern exists about the possible toxic effects of chromium picolinate. The aim of this study was to determine the effect of chromium treatment in the form of chromium yeast on glycemic control in a Western population of patients with type 2 diabetes who were being treated with oral hypoglycemic agents.RESEARCH DESIGN AND METHODS -In this 6-month, double-blind study, patients with moderate gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 31 publications
1
62
0
1
Order By: Relevance
“…They included both type 1 and type 2 DM, gestational DM, and even steroid-induced diabetes. In the present meta-analysis, four studies showed that Cr has no significant effect on HbA1c (13,15,16,19). In two other studies (17,18), a 0.7% and 1.16% reductions in HbA1c was reported for Cr, respectively.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…They included both type 1 and type 2 DM, gestational DM, and even steroid-induced diabetes. In the present meta-analysis, four studies showed that Cr has no significant effect on HbA1c (13,15,16,19). In two other studies (17,18), a 0.7% and 1.16% reductions in HbA1c was reported for Cr, respectively.…”
Section: Discussionmentioning
confidence: 48%
“…The summary for effect size of weighted mean differences of BMI change "∆BMI" in diabetic patients in Cr supplement therapy for six included trials comparing to Pl retrieved from five studies (13,(15)(16)(17)19) was -0.07 with 95% CI= -0.37 to 0.23 (P= 0.66, Figure 9-a). The Cochrane Q test for heterogeneity indicated that the studies are not heterogeneous (P= 0.73) and could be combined, thus the fixed effects for individual and summary of effect size for weighted mean differences was applied.…”
Section: Effect Of Cr On Bmi In Diabetic Patientsmentioning
confidence: 99%
“…Chromium supplementation may be beneficial in rare cases of prolonged total parental nutrition when standard chromium supplementation is lacking [6] . Despite the lack of sufficient evidence that chromium supplementation improves glycemic control [28,29] , chromium is still widely marketed as an effective supplement for improving glycemic control in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Significant effects in the meta-analysis were only found in studies with poor methodological quality or in studies sponsored by chromium supplement producing companies. In addition, the effects of chromium supplementation were shown to be absent or non-relevant after stratifying the studies according to methodological quality, sponsor involvement, and a western vs non-western study location [6,29] . After the review written by Balk et al [28] , a second Dutch double blind trial was performed in 2008 that studied the effects of chromium on HbA1c levels in patients with type 2 diabetes [29] .…”
Section: Clinical Evidence For Chromium Usementioning
confidence: 99%
See 1 more Smart Citation